Strategi komunikasi PT Permodalan Nasional Madani Dalam Mempertahankan Reputasi Perusahaan Melalui Media Massa dan Media Sosial - Sularto Aras Hamka; Sri Wahyuni (ijd-demos, 2026)
This study investigates the communication strategies used by PT PNM to maintain its corporate reputation through mass media and social media while exploring the challenges encountered across these communication channels. The research adopts the Harris–Fombrun Corporate Reputation Quotient (CRQ), which consists of six dimensions: emotional appeal, products and services, vision and leadership, workplace environment, financial performance, and social responsibility. A qualitative approach was employed, with data collected through interviews with the Head of the Corporate Secretariat Division and the Head of Corporate Communication. The results indicate that PT PNM consistently applies an integrated communication strategy that strengthens corporate values, financial credibility, leadership, and social responsibility. Although communication challenges remain, the company effectively sustains stakeholder trust and reinforces its long-term corporate reputation in a dynamic and evolving media environment. Keywords: Communication Strategy, Corporate Reputation, Mass Media, Social Media.